IMPLEMENTASI PROGRAM MADRASAH TAHFIDZ KEMENAG DIY DI MADRASAH ALIYAH NEGERI SE-KOTA YOGYAKARTA - Afiq Fikri Almas; Imam Machali (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Abstract: The Implementation of Madrasa Tahfidz program of Ministry of Religion DIY has not been evenly distributed. This was the basis for the researchers to evaluate the program especially in MAN 1 and MAN 2 Yogyakarta. This evaluation research used an objective-oriented approach to measure the objective level of achievement program and used mixed methods with a concurrent embedded model. The CIPPO (Context, Input, Process, Product, and Outcome) evaluation model was used to analyze the program. The researcher used purposive sampling and snowballing sampling techniques in determining the subjects. The results show that overall the Madrasa Tahfidz program was quite effective because input, process, and outcomes of evaluated CIPPO components were optimally fulfilled. It is produce recommendations for revising the program, because there are still 2 components cannot be assessed as effective and still need continuous improvement. Context has not been effective because student need components are more needed in improving of reading Quran rather than memorizing. The product of program is not yet effective because referring to three measuring instruments that produce an average measurement result at a moderate level with a percentage (46.6%), either by sex, origin of madrasa and class of students, and haven’t reached a high level. Abstrak: Implementasi program Madrasah Tahfidz Kementerian Agama DIY belum merata antara satu madrasah dan lainnya. Hal inilah yang menjadi dasar bagi peneliti untuk mengevaluasi program tersebut terutama di MAN 1 dan MAN 2 Yogyakarta. Penelitian evaluasi ini menggunakan pendekatan yang berorientasi pada tujuan untuk mengukur tingkat pencapaian program dan menggunakan metode campuran dengan model concurrent embedded. Model evaluasi CIPPO (Context, Input, Process, Product, and Outcome) digunakan untuk menganalisis program. Peneliti menggunakan purposive sampling dan teknik snowballing sampling dalam menentukan subjek yang berkualitas. Hasil penelitian menunjukkan bahwa efektivitas keseluruhan program Madrasah Tahfidz